Tacit Significance, Explicit Irrelevance: The Use of Language and Silence in The Caretaker and The Dumb Waiter - Saravia Vargas, Juan Carlos (2013)
Readers who approach the Theater of the Absurd face complex interpretive problems. The style of Harold Pinter, the laureate British playwright, adds an additional difficulty due to his particular use of language. His plays The Caretaker and The Dumb Waiter show how speech is overshadowed by silence, which provides a more direct access to the tortured psyche of characters.